MNM: A Collective Love Letter by and to Musicians - Culver, Andrew (Circuit, 2004)
Culver presents his observations and reactions to the first MNM Festival, and then opens the suggestion box with his views on the steps MNM should take to solidify it's survival and relevancy. Finally, he compares the festival to it's potential place in the history of culture, technology and music since Monteverdi/Gutenberg through Cage/McLuhan and into the future.